2021
DOI: 10.3390/nu13030815
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-Induced Effects on Human Skeletal Muscle Contraction Time and Maximal Displacement Measured by Tensiomyography

Abstract: Studies on muscle activation time in sport after caffeine supplementation confirmed the effectiveness of caffeine. The novel approach was to determine whether a dose of 9 mg/kg/ body mass (b.m.) of caffeine affects the changes of contraction time and the displacement of electrically stimulated muscle (gastrocnemius medialis) in professional athletes who regularly consume products rich in caffeine and do not comply with the caffeine discontinuation period requirements. The study included 40 professional male ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 60 publications
0
24
2
2
Order By: Relevance
“…This effect is possibly achieved by caffeine acting as an antagonist of the adenosine receptor subtype A 1 on the skeletal muscle membrane or/and attachment to ryanodine receptors (RyRs) on the sarcoplasmic reticulum (SR) [ 23 , 24 ]. Besides the greater release of Ca 2+ , increased myofibrillar Ca 2+ sensitivity, improved SR Ca 2+ permeability, and decreased activity of the SR Ca 2 pump are attained, ultimately resulting in modified muscle performance [ 24 , 25 ]. Furthermore, studies have shown that caffeine administration leads to an increase in circulating epinephrine, norepinephrine, cortisol, plasma lactate, whereas the plasma beta-endorphin can increase by almost two-fold [ 26 ].…”
Section: Ed Ingredients—caffeine and Taurine Contributionmentioning
confidence: 99%
“…This effect is possibly achieved by caffeine acting as an antagonist of the adenosine receptor subtype A 1 on the skeletal muscle membrane or/and attachment to ryanodine receptors (RyRs) on the sarcoplasmic reticulum (SR) [ 23 , 24 ]. Besides the greater release of Ca 2+ , increased myofibrillar Ca 2+ sensitivity, improved SR Ca 2+ permeability, and decreased activity of the SR Ca 2 pump are attained, ultimately resulting in modified muscle performance [ 24 , 25 ]. Furthermore, studies have shown that caffeine administration leads to an increase in circulating epinephrine, norepinephrine, cortisol, plasma lactate, whereas the plasma beta-endorphin can increase by almost two-fold [ 26 ].…”
Section: Ed Ingredients—caffeine and Taurine Contributionmentioning
confidence: 99%
“…The criterion of "physically active subjects" was used when they did physical activity at least two days a week (1-2 h per session), did not participate in competitive-level sport and had not followed any specific training programme in the previous three months. No participant had consumed supplements to increase muscle mass and improve strength nor did they consume more than 60 mg of caffeine per day (~1 cup of coffee) to avoid the effect of caffeine on the variables analyzed [19,20]. The women included in the study were always tested in the luteal phase.…”
Section: Participantsmentioning
confidence: 99%
“…Caffeine may also have a direct positive effect on the mechanical activity of skeletal muscle. This was demonstrated by Domaszewski et al [ 187 ], who studied 40 professional male handball players (age: 23.13 ± 3.51 years, body mass: 93.51 ± 15.70 kg, height: 191 ± 7.72 cm, BMI: 25.89 ± 3.10) who regularly consumed products rich in caffeine by giving them caffeine at a dose of 9 mg/kg body weight. The authors observed improved contraction time and reduced maximal displacement in the tested group [ 187 ].…”
Section: The Role Of Caffeine In Various Systems In the Human Bodymentioning
confidence: 88%